Study on best extraction process parameters of semi-refined carrageenan from kappaphycus alvarezii seaweed - Muhammad Amirulhusni, Abdul Hadi (2024)
This thesis presents a comprehensive study on the optimization of extraction process parameters to produce semi-refined carrageenan from Kappaphycus alvarezii seaweed in Sabah. Carrageenan, a natural polysaccharide derived from seaweeds, has gained significant industrial importance due to its diverse applications in various sectors, including food, pharmaceuticals, and cosmetics. However, the variations in gelling properties can result in inconsistent production of biodegradable plastic and affect the quality and functionality of the biopolymers. There is a need to optimize the extraction process of carrageenan from seaweed that can improve the quality and yield of carrageenan while minimizing the use of harsh chemicals and reducing the environmental impact. Therefore, the knowledge of the best extraction parameter for carrageenan production with targeted high gelling properties is still limited. Therefore, the aim of the study is to determine the best extraction process parameters for the semi-refined carrageenan production of Kappaphycus alvarezii seaweed from Sabah. This investigation started with collecting a sample of the seaweed, which is from Sabah. These samples will then be extracted with conditions of KOH concentration (6% and 12%), extraction time (1 and 3 hours), temperature (60 and 80 °C), and soaking time (0 and 14 days) using Design Expert. Then, the biodegradable packaging film will be synthesized from 2% w/w plasticized SRC, adding 0.9% natural plasticizer (glycerol) enhanced with 10% cellulose nanofibers (CNF). The film will be analyzed for its significant response via moisture content and viscosity. The thermal properties of semi-refined carrageenan-based packaging film will be characterized by mechanical properties such as tensile strength (TS) and elongation at break (EAB).